Co-constructing utterances in face-to-face-interaction: A multimodal analysis of collaborative completions in spoken Spanish - Kalkhoff, Alexander Teixeira; Dressel, Dennis (Social Interaction. Video-Based Studies of Human Sociality, 2019)
This article examines collaborative utterances in interaction from a multimodal perspective. Whereas prior research has analyzed co-constructions ex post as the result of local speaker collaboration on the basis of audio data, this study shifts the focus to co-constructing as a highly coordinated, embodied practice. By examining video data of Spanish interactions, this research aims to show how speakers systematically deploy a variety of linguistic and bodily resources that serve as points of joint orientation throughout the process of co-constructing utterances.